Differential impact of heat and hypoxia on dynamic oxygen uptake and deoxyhemoglobin parameters during incremental exhaustive exercise - Geng, Zhizhong; Wang, Jinhao; Cao, Guohuan; Tan, Chenhao; Li, Longji; Qiu, Jun (Frontiers in Physiology, 2024)
Purpose: This study aims to explore the relationship between the dynamic changes in oxygen uptake (V̇O2) and deoxyhemoglobin (HHb) and peripheral fatigue in athletes during incremental exhaustive exercise under different environmental conditions, including high temperature and humidity environment, hypoxic environment, and normal conditions. Methods: 12 male modern pentathlon athletes were recruited and performed incremental exhaustive exercise in three different environments: normal condition (23℃, 45%RH, FiO2=21.0%, CON), high temperature and humidity environment (35℃, 70%RH, FiO2=21.0%, HOT), and hypoxic environment (23℃, 45%RH, FiO2=15.6%, HYP). Gas metabolism data of the athletes were collected, and muscle oxygen saturation (SmO2) and total hemoglobin content in the vastus lateralis muscles (VL) were measured to calculate the deoxyhemoglobin content. Linear and nonlinear function models were used to fit the characteristic parameters of V̇O2 and HHb changes. Results: The results showed that compared to the CON, V̇O2, V̇CO2, and exercise time were decreased in the HOT and HYP (P＜0.05). ΔEV̇O2 and OUES were reduced in the HOT and HYP compared to the CON (P＜0.05). The Gas exchange threshold in the CON corresponded to higher V̇O2 than in the HYP and HOT (P＜0.05). ΔEV̇O2-1 was reduced in the HOT compared to the HYP (P＜0.05). ΔEHHb was higher in the HOT compared to the CON (P＜0.05). ΔEHHb-1 was increased in the HYP compared to the CON (P＜0.05). There was a negative correlation between ΔEHHb and corresponding V̇O2max in the HOT (r=-0.655, P＜0.05), and a negative correlation between ΔEHHb-1 and corresponding V̇O2max in the HYP (r=-0.606, P＜0.05). Conclusion: Incremental exhaustive exercise in hypoxic environment and high temperature and humidity environments inhibits gas exchange and oxygen supply to skeletal muscle tissue in athletes. For athletes, the accelerated deoxygenation response of skeletal muscles during incremental exhaustive exercise in high temperature and humidity environments, as well as the excessive deoxygenation response before BP of deoxyhemoglobin in hypoxic environment, may be contributing factors to peripheral fatigue under different environmental conditions.